The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/hmg/ddr107
|View full text |Cite
|
Sign up to set email alerts
|

The ATRX-ADD domain binds to H3 tail peptides and reads the combined methylation state of K4 and K9

Abstract: Mutations in the ATRX protein are associated with the alpha-thalassemia and mental retardation X-linked syndrome (ATR-X). Almost half of the disease-causing mutations occur in its ATRX-Dnmt3-Dnmt3L (ADD) domain. By employing peptide arrays, chromatin pull-down and peptide binding assays, we show specific binding of the ADD domain to H3 histone tail peptides containing H3K9me3. Peptide binding was disrupted by the presence of the H3K4me3 and H3K4me2 modification marks indicating that the ATRX-ADD domain has a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 34 publications
7
110
0
Order By: Relevance
“…All CG8290 isoforms share a common N-terminal ADD domain (amino acids . The ADD domain has been reported to confer binding to histone tails and is present in the well-studied mammalian proteins ATRX and DNMT3a (Dhayalan et al 2011;Eustermann et al 2011;Iwase et al 2011). Recently, it was shown that in the context of human ATRX, the ADD domain binds the histone H3 tail, specifically the H3K4me0K9me2/3 modification.…”
Section: Cg8290 Exhibits Affinity For H3k9me2/3 Through An Atrx-like mentioning
confidence: 99%
See 1 more Smart Citation
“…All CG8290 isoforms share a common N-terminal ADD domain (amino acids . The ADD domain has been reported to confer binding to histone tails and is present in the well-studied mammalian proteins ATRX and DNMT3a (Dhayalan et al 2011;Eustermann et al 2011;Iwase et al 2011). Recently, it was shown that in the context of human ATRX, the ADD domain binds the histone H3 tail, specifically the H3K4me0K9me2/3 modification.…”
Section: Cg8290 Exhibits Affinity For H3k9me2/3 Through An Atrx-like mentioning
confidence: 99%
“…Recently, it was shown that in the context of human ATRX, the ADD domain binds the histone H3 tail, specifically the H3K4me0K9me2/3 modification. This recognition was enhanced by interaction with HP1a, which also recognizes the same epitope, although likely on a neighboring nucleosome (Dhayalan et al 2011;Iwase et al 2011). Given that the fly homolog of ATRX, XNP, lacks an ADD domain (Bassett et al 2008;Valadez-Graham et al 2012), we wanted to explore the possible link between the CG8290 ADD, HP1a, and H3K9me2/3 recognition.…”
Section: Cg8290 Exhibits Affinity For H3k9me2/3 Through An Atrx-like mentioning
confidence: 99%
“…This comprises a PHDlike zinc finger and an additional C 2 C 2 motif just upstream, which is structurally similar to the GATA1 zinc fingers (Gibbons et al 1997;Argentaro et al 2007) and is highly related to the zinc finger domains of DNA methyltransferases (Argentaro et al 2007). The domain mediates binding to the amino-terminal tail of histone H3 trimethylated at lysine 9 (Dhayalan et al 2011;Eustermann et al 2011;Iwase et al 2011). The functional importance of the ADD segment in ATRX is clear.…”
Section: Characterization Of the Atrx Gene And Its Protein Productmentioning
confidence: 99%
“…12 A recent study confirms that the ADD domain of ATRX interacts with histone H3 tails that are trimethylated at lysine 9. 25 To further examine whether ATRX directly contributes to the pathological process in HD, we developed a Drosophila model of ATRX/dXNP and characterized its physiological effects by crossing ATRX/dXNP and mtHtt (127Q) flies. We found that knockdown of ATRX increased the hatching rate and reduced egg deformations caused by mtHtt (127Q).…”
Section: Discussionmentioning
confidence: 99%